Multiwalled Carbon Nanotubes Modified with Biocompatible Compounds - Bolbukh, Y.; Gunko, G.; Prikhod’ko, G.; Tertykh, V.; László, K.; Tóth, A.; Koczka, B. (Хімія, фізика та технологія поверхні, 2010)
Oxidized with solution of hydrogen peroxide multiwalled carbon nanotubes (MWCNTs) were modified with 2-hydroxyethylmethacrylate (HEMA) or chitosan (CTS). Morphology and surface properties of the pristine and modified MWCNTs have been investigated. The zeta-potential behaviour of MWCNTs was studied as a function of pH and suspension concentration. After oxidation, the divided nanotubes are found to have uncapped ports decorated with hydroxyl groups mostly. Surface oxygencontaining groups specify the negative zeta-potential in all pH range studied (pH=3-11). The values of zeta-potential display an inverse dependence on the dispersion concentration in acidic and basic solutions. After modification of oxidized MWCNTs with HEMA their isoelectric point is shifted from pH=2 to pH=10. Repeated surface treatment with HEMA (MWCNTs-HEMA-HEMA), along with change of the nature of terminal groups, provides stable surface charge increasing with nanotubes concentration in the pH range of 3-9. The isoelectric point of MWCNTs modified with CTS occurs at pH=4.5. At relatively small zeta-potential values, which become more negative with a decrease in the nanotubes concentration, such suspensions are the most stable.